2019
DOI: 10.1111/bjh.15889
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of cachexia on clinical outcomes in aggressive lymphoma

Abstract: Summary Cancer cachexia is a state of involuntary weight loss and altered body composition triggered by an underlying malignancy. We sought to correlate measures of cachexia with clinical outcomes in aggressive lymphomas and to identify biological pathways involved in the cachexia phenotype for possible druggable targets. Radiographic measures of cachexia were collected in a retrospective cohort of 109 patients with aggressive B‐cell lymphoma and followed for clinical outcome. We found males with sarcopenia ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 31 publications
1
24
1
Order By: Relevance
“…The impact of cancer cachexia on clinical outcomes has been evaluated in males versus females. For example, Burkart et al [30] investigated a cohort of 109 patients with aggressive B cell lymphoma. They reported that both progression-free survival (PFS) and overall survival (OS) were decreased in males with sarcopenia compared with those without and that males with adipopenia had decreased OS compared with the non-adipopenic group.…”
Section: Sex Difference In Cancer Cachexia Phenotypesmentioning
confidence: 99%
“…The impact of cancer cachexia on clinical outcomes has been evaluated in males versus females. For example, Burkart et al [30] investigated a cohort of 109 patients with aggressive B cell lymphoma. They reported that both progression-free survival (PFS) and overall survival (OS) were decreased in males with sarcopenia compared with those without and that males with adipopenia had decreased OS compared with the non-adipopenic group.…”
Section: Sex Difference In Cancer Cachexia Phenotypesmentioning
confidence: 99%
“…Given the high tumor burden of DLBCL and the favorable response rate with substantial treatmentrelated toxicities of R-CHOP treatment, the prognostic role of cancer cachexia is also likely to be observed in DLBCL patients. Several markers for malnutrition and cachexia such as body mass index (BMI), sarcopenia, adipopenia, and serum albumin level have been studied and suggested to be prognostic factors in DLBCL [14][15][16][17]. Additionally, the clinical value of the Geriatric Nutritional Risk Index (GNRI), which was originally developed to predict nutrition-related morbidity and mortality in non-cancer patients [18], was evaluated in two previous DLBCL studies with conflicting results [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors found that a decreased muscle mass was independently associated with lower overall survival and progression-free survival in DLBCL patients (5,(7)(8)(9). Others confirmed this result in male patients only (10,11), while Chu et al (6,12) described a trend toward an improved survival in patients with lower SMI.…”
Section: Introductionmentioning
confidence: 95%